Model Pemberdayaan Kesehatan Masyarakat melalui Taman Gizi Hismawati Perguruan Islam Mathali’ul Falah Kajen Margoyoso Pati - Laili, Nadia Maunatul; Niam, Muhamad Mulin (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
The community health empowerment model is an approach that aims to improve community welfare in the health sector. Community empowerment can be carried out by various parties, one of which is through school-based organizations, namely Taman Gizi of HISMAWATI, Mathali'ul Falah Islamic School, Kajen Margoyoso Pati. This organization focuses on community health empowerment through its programs. This research aims to determine the model of community health empowerment carried out by Taman Gizi of HISMAWATI. The method used in this study is descriptive qualitative with the type of field research, data collection techniques using interviews and documentation, while data analysis techniques use the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and drawing conclusions. The research results show that the model of community health empowerment implemented by Taman Gizi of HISMAWATI is school-based participatory empowerment. Based on Jim Ife's empowerment theory used in this research, the concept of community health empowerment carried out by Taman Gizi of HISMAWATI is providing resources, opportunities, knowledge and skills in the form of facilitating the Kajen Village community and PIM female students through its programs. In this model, the objectives of empowerment include four improvements, namely institutional improvement, business improvement, environmental improvement and life improvement. The empowerment strategy used include the empowerment level, namely the micro level and the empowerment approach which including five approaches, namely the enabling, strengthening, protection, support and maintenance. Meanwhile, the empowerment principles used include four principles, namely the principle of equality, the principle of participation, the principle of independence and the principle of sustainability.